Developing self-esteem-based curriculum as a foundation for sustainable education: A systematic literature review and bibliometric analysis - Nuryana, Zalik; Xu, Wenbin; Lu, Shiqi (Frontiers in Education, 2023)
This study aimed to analyze the thematic structure and trends in scientific publications discussing the relationship between curriculum development and self-esteem and provide a roadmap for future research investigating this topic. This study used systematic literature review (SLR) and bibliometric analysis (BA) to describe self-esteem-based curriculum development and reveal its bibliometric profile. The data were obtained from the 2012-2021 Scopus database by identifying the research on curriculum and self-esteem, so the keywords used are ("curriculum development" or "curriculum") and ("self-esteem" or "self esteem"). The results show that the publication examining the curriculum and self-esteem leads to stable total publication. Countries contributing to this topic are the United States, the United Kingdom, Australia, India, and South Africa. Meanwhile, the universities mostly credited with high citations on this topic are Monash University, the Ohio State University, and Universidad de Malaga. This study discovers that most articles about curriculum and self-esteem discuss health sciences/medicine, psychology, and education. The results discover the structure and trends in thematic academic studies to provide a roadmap for future studies investigating curriculum development and self-esteem. Curriculum and self-esteem will affect the instructional practices at schools to be better by developing self-esteem through the curriculum. In this context, educational researchers should interconnect their scientific field with psychology, specifically self-esteem. Therefore, the development of a self-esteem-based curriculum can run well. This paper attempted to gain insights into how research on curriculum and self-esteem has progressed using the systematic literature review and bibliometric analysis.